Penetrating Heart Injury due to Screwdriver Assault - P. A. Dieng; M. S. Diop; A. G. Ciss; P. S. Ba; S. Diatta; M. Gaye; M. L. Fall; A. Ndiaye; M. Ndiaye (Case Reports in Cardiology)
Penetrating heart injuries cause wounds in the cardiac chambers. Most of them are due to gunshot or stabbing by knives. Screwdriver is an uncommon weapon. Authors report a case of stab wound by screwdriver, treated at cardiovascular center in Dakar. This is a 16-year-old boy who experienced physical aggression. He was assaulted with a screwdriver and had stab wound on the anterior wall of the chest. Physical examination showed a screwdriver penetrating the sternum bone over a right angle. He had a mild pericardial blood effusion and a right ventricle wound 5 mm in diameter with transection of the right coronary vein. The screwdriver was removed without cardiopulmonary bypass (CPB) and the ventricle wound repaired by direct suture of stitches reinforced with Teflon pledgets. The right coronary artery was ligated. Postoperative period was free of events. Screwdriver is uncommonly used as a weapon. It is a dangerous device because of its rigid structure and narrow tip.